2021
DOI: 10.1038/s41467-021-26634-9
|View full text |Cite
|
Sign up to set email alerts
|

The composition of human vaginal microbiota transferred at birth affects offspring health in a mouse model

Abstract: Newborns are colonized by maternal microbiota that is essential for offspring health and development. The composition of these pioneer communities exhibits individual differences, but the importance of this early-life heterogeneity to health outcomes is not understood. Here we validate a human microbiota-associated model in which fetal mice are cesarean delivered and gavaged with defined human vaginal microbial communities. This model replicates the inoculation that occurs during vaginal birth and reveals last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 116 publications
0
41
0
Order By: Relevance
“…On the other hand, maternal gut strains are more enduring in the baby’s gut and are better ecologically adapted [ 38 , 39 ]. During pregnancy, the bacterial diversity in the vagina is low but stable.…”
Section: Maternal Fetal and Neonatal Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, maternal gut strains are more enduring in the baby’s gut and are better ecologically adapted [ 38 , 39 ]. During pregnancy, the bacterial diversity in the vagina is low but stable.…”
Section: Maternal Fetal and Neonatal Microbiotamentioning
confidence: 99%
“…Offspring born from vaginal delivery and whose mothers were vaginally colonized with Lactobacillus during pregnancy had increased ratios of CD45RO+ cells and lower IL-12 levels in cord blood, indicating that lactobacilli in the vagina impacted fetal immune development. It is a possibility that this influence could be attributable to bacterial metabolites, ascending organisms, or the dependence of the vaginal microbiome on the gut microbiota [ 38 , 39 ].…”
Section: Maternal Fetal and Neonatal Microbiotamentioning
confidence: 99%
“…We used our C-section and oral gavage protocol to inoculate mouse pups with either CST I or CST IV and assessed outcomes across development and into adulthood. Birth-associated exposure to CST I and CST IV resulted in transient colonization of the intestinal tract in C-section delivered mice and was sufficient to elicit CST-specific transcriptional signatures in the neonatal ileum, as well as sex-specific differences in adulthood [ 57 ]. Epidemiological studies demonstrated that maternal obesity and presence of vaginal G. vaginalis are two common risk factors associated with increased risk for adverse obstetric outcomes [ 58 63 ].…”
Section: Influence Of the Prenatal Maternal Microbiome On Neonatal He...mentioning
confidence: 99%
“…Epidemiological studies demonstrated that maternal obesity and presence of vaginal G. vaginalis are two common risk factors associated with increased risk for adverse obstetric outcomes [ 58 63 ]. We established a two-hit model to determine whether maternal obesity and presence of vaginal G. vaginalis , alone or in combination, would affect the offspring postnatal response to CST I or CST IV exposure at birth [ 57 ]. Surprisingly, neonates that gestated in a two-hit environment showed a pathological immune response and decreased survival following exposure to CST IV, a pattern that was not observed in CST I exposed offspring.…”
Section: Influence Of the Prenatal Maternal Microbiome On Neonatal He...mentioning
confidence: 99%
See 1 more Smart Citation